2017
DOI: 10.4172/2375-4389.1000260
|View full text |Cite
|
Sign up to set email alerts
|

Economic Challenges and Opportunities after the Revolution in Tunisia: Inflation and Exchange Rate

Abstract: The African Development Bank Group suggest that structural challenges are needed to moving up the value chain through structural shift of the manufacturing sector and the liberalization of the domestic private sector from the dual economy. However, exchange rates and capital accounts are still under the strict control of the Central Bank, even though exceptions are accorded to export-related activities. The public sector dominates all the strategic sectors in the economy (e.g., energy, transport, telecommunica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Several previous studies and theories say that exchange rates, inflation, and economic growth have a causal relationship. The study by Loukil (2017) concluded that there is a unidirectional causal relationship between inflation and the exchange rate in Tunisia. Lado's (2015) research found that there is a two-way causality between inflation and exchange rates in South Sudan.…”
Section: Figure 1 Exchange Rate (Usd/idr) Inflation and Economic Grow...mentioning
confidence: 99%
“…Several previous studies and theories say that exchange rates, inflation, and economic growth have a causal relationship. The study by Loukil (2017) concluded that there is a unidirectional causal relationship between inflation and the exchange rate in Tunisia. Lado's (2015) research found that there is a two-way causality between inflation and exchange rates in South Sudan.…”
Section: Figure 1 Exchange Rate (Usd/idr) Inflation and Economic Grow...mentioning
confidence: 99%